2021
DOI: 10.3892/ol.2021.13101
|View full text |Cite
|
Sign up to set email alerts
|

Integrative meta‑analysis of gene expression profiles identifies FEN1 and ENDOU as potential diagnostic biomarkers for cervical squamous cell carcinoma

Abstract: Cervical carcinoma is a global public health burden. Given that it is usually asymptomatic at potentially curative stages, the development of clinically accurate tests is critical for early detection and individual risk stratification. The present study performed an integrative meta-analysis of the transcriptomes from 10 cervical carcinoma cohorts, with the aim of identifying biomarkers that are associated with malignant transformation of cervical epithelium, and establish their clinical applicability. From am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Flap endonuclease‐1 (FEN1), a prototypical member of the RAD2‐superfamily required for proficient DNA replication and the repair of DNA damage, is one of the key tumor suppressor targets for HNSCC predicted by our research group 13 . Interestingly, multiple recent studies have implicated its association with immune response inhibition 14,15 . More surprisingly, in our recent study, we found that overexpressed FEN1 in the tissues and cells of HNSCC was detected, which was associated with an inhibitory immune microenvironment; down‐regulation of FEN1 could not only inhibit PD‐L1 expression, but also exhibit a potential effect on upregulating HLA expression through the interference gamma (IFN‐γ)/Janus kinase (JAK)/signal transmitter and activator transcription 1 (STAT1) pathway 16 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Flap endonuclease‐1 (FEN1), a prototypical member of the RAD2‐superfamily required for proficient DNA replication and the repair of DNA damage, is one of the key tumor suppressor targets for HNSCC predicted by our research group 13 . Interestingly, multiple recent studies have implicated its association with immune response inhibition 14,15 . More surprisingly, in our recent study, we found that overexpressed FEN1 in the tissues and cells of HNSCC was detected, which was associated with an inhibitory immune microenvironment; down‐regulation of FEN1 could not only inhibit PD‐L1 expression, but also exhibit a potential effect on upregulating HLA expression through the interference gamma (IFN‐γ)/Janus kinase (JAK)/signal transmitter and activator transcription 1 (STAT1) pathway 16 .…”
Section: Introductionmentioning
confidence: 80%
“…13 Interestingly, multiple recent studies have implicated its association with immune response inhibition. 14,15 More surprisingly, in our recent study, we found that overexpressed FEN1 in the tissues and cells of HNSCC was detected, which was associated with an inhibitory immune microenvironment; down-regulation of FEN1 could not only inhibit PD-L1 expression, but also exhibit a potential effect on upregulating HLA expression through the interference gamma (IFN-γ)/Janus kinase (JAK)/signal transmitter and activator transcription 1 (STAT1) pathway. 16 These studies indicate potential links between FEN1 inhibition and enhanced antitumor immunity.…”
Section: Introductionmentioning
confidence: 95%
“…EndoU family of endonucleases have been implicated in many processes, including as a tumor biomarker in human beings 77 79 , immune response in mice 51 , ER morphology in Xenopus 80 , neurodegeneration in Drosophila 50 , cold tolerance, nucleotide metabolism, lifespan and germline immortality in C. elegans 61 , 81 , 82 , and viral replication and pathogenicity 83 85 . Our findings reveal another role of EndoU family proteins in lipolysis and provide mechanistic insights for such a specific function.…”
Section: Discussionmentioning
confidence: 99%
“…However, its reliability is debatable due to its dependence on human interpretation ( Long et al, 2017 ). Despite several alternate cervical cancer screening methods proposed over the years such as cytological testing alone, standalone hrHPV testing, and cytological + hrHPV combination testing (co-testing) ( Curry et al, 2018 ; Kim et al, 2018 ; Terasawa et al, 2022 ), the 5 years survival rate remains a dismal 66% ( Long et al, 2017 ; Basic et al, 2021 ; Qu et al, 2021 ; Hou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%